Saint Jovan Bigorski - A Macedonian Orthodox Cultic Place - Cacanoska, Ruzica (Occasional papers on religion in Eastern Europe, 2015)
The subject matter of this paper is the socio-historical analysis of the cult1 life of the Saint Jovan (John) Bigorski Monastery. This subject matter will be elaborated by developing a historical frame wherewith the sociological research element will be merged; this element will specifically emphasize the impact of the miraculous icon on the promotion and cultic life of the Saint Jovan Bigorski Monastery.